HUBUNGAN SISTEM PENGELOLAAN ZAKAT PROFESI MENURUT SURAT AT-TAUBAH AYAT 103 DAN UU NO.23 TAHUN 2011 DI INDONESIA - Dr. Sulthan MH.; fahrurrizal fahrurrizal SH. (VERITAS, 2018)
That the zakat of the profession is compulsory, equal to zakah and other incomesuch as agriculture, livestock and trade. The limit of nisab assets obtained from theprofession business can be equated nisabnya with zakat crops that is 5 wasaq(about 750 kg of rice), with a zakat obligation of 5% or 10%, and paid whengaining the rewards or wages of the profession. For professions that are notclassified as "a collar white", whose income is not so great, as doctors in hospitals,teachers or lecturers who only receive a fixed salary from the government agencywhere it works, likened nisabnya with gold and silver nisab , which is 93.6 grams,with a zakat obligation of 2.5 percent, issued every one year, and after expenditureof basic needs. Well integrated with zalcat management system in a consistent andsustainable manner. There is a relationship between Surat At-Taubah paragraph103 is very relevant to Law No. 23. Year 2011 in the implementation of zakat inIndonesia, taken from someone's property, including in it the property of one'sprofession